Activating inverse spinel NiCo2O4 embedded in N-doped carbon nanofibers via Fe substitution for bifunctional oxygen electrocatalysis. (March 2021) - Wang, A.; Hu, Y.; Wang, H.; Cheng, Y.; Thomas, T.; Ma, R.; Wang, J.
Abstract: To improve the structure-dominant activity, rational design of oxide-based materials remains challengeable in bifunctional oxygen electrocatalysis, especially from the perspective of electronic modulation. Herein, we demonstrate that the electron configuration of inverse spinel NiCo2 O4 can be activated by controllable substitution of Fe into the octahedral centers. Fe-substituted NiCo2 O4 nanoparticles embedded in porous N-doped carbon nanofibers (NiCo2- x Fe x O4 /NCNF), which were synthesized by scalable electrospinning, exhibit a correlated relationship with Fe atomic content and achieve an optimal bifunctional activity (ΔE = 0.74 V) at 0.25 at.%. Theoretical calculation shows that the substitution of Co 3+ by Fe 3+ modulates the electrons filling in eg orbital of octahedral cation via delocalizing the electrons around O anions. The increased density of states around the Fermi level further regulate the adsorption energy of oxygen intermediates and lead to better bifunctional performance than commercial Pt/C + RuO2 in rechargeable Zn-air battery. This work provides a new pathway to develop cost-effective bifunctional electrocatalysts for electrochemical energy storage and conversion. Graphical abstract: Image 1 Highlights: Fe-doped NiCo2 O4 nanoparticles within porous N-doped carbon nanofibers (NiCo2-x Fex O4 /NCNFs) are fabricated via electrospinning and subsequent annealing. The optimized NiCo1.75 Fe0.25 O4 /NCNF shows much lower potential difference (ΔE) of 0.74 V than commercial Pt/C + RuO2 mixture (1.05 V). Theoretical calculation reveals that [Fe 3+ ]Oct induces the transformation of Co 3+ ions from low spin to intermediate spin state. NiCo1.75 Fe0.25 O4 /NCNF in zinc-air battery shows a low discharge-charge voltage gap and robust stability over 300 cycles at 10 mA cm −2 .